Adding Crowd Noise to Sports Commentary using Generative Models - Shah, Neil; Agrawal, Dharmeshkumar M.; Pedanekar, Niranajan (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2021: Proceedings of the 1st Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2021.15715, 2021)
Crowd noise forms an integral part of a live sports experience. In the post-COVID era, when live audiences are absent, crowd noise needs to be added to the live commentary. This paper exploits the correlation between commentary and crowd noise of a live sports event and presents an audio stylizing sports commentary method by generating live stadium-like sound using neural generative models. We use the Generative Adversarial Network (GAN)-based architectures such as Cycle-consistent GANs (Cycle-GANs) and Mel-GANs to generate live stadium-like sound samples given the live commentary. Due to the unavailability of raw commentary sound samples, we use end-to-end time-domain source separation models (SEGAN and Wave-U-Net) to extract commentary sound from combined recordings of the live sound acquired from YouTube highlights of soccer videos. We present a qualitative and a subjective user evaluation of the similarity of the generated live sound with the reference live sound.